The Persuasive speech in business advertorial discourse - Anastasia Baan (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2022)
The study outlined in this article aimed to describe the language used in the advertisements discourse in the online daily news. This study analyzed the persuasive language used in the business advertorial which includes the choice of language forms and persuasion techniques in advertorial discourses that have persuasive power. The study was designed using a qualitative approach. The data source was the business advertorials text contained in online news media. Data of the study is in the form of words and sentences that are considered to have persuasive power in influencing the targeted audience. By applying content analysis, this study produced findings on language characteristics and persuasive techniques found in business advertorial discourses. The persuasive language forms in the advertorial discourses were represented in the choice of words and expressions. The persuasive words illustrated profits, self-image, heart responses. The style of words was hyperbolic, metaphorical, and language prestige. The expressions in the advertorial discourses have the meaning of suggestions for prospective customers, demeaning other products, emphasizing self-confidence, emphasizing product competition, giving evidence of product trust, and expressions to invite action. The words and expressions were chosen according to the context and product advertised to emphasize the emotional meaning of the ad reader. The persuasion techniques were used to achieve a number of changes, such as changing the knowledge, attitudes, and behavior of the readers.